Inclusion of salt form on prescription medication labeling as a source of patient confusion: a pilot study - McDougall DJ; Hoehns JD; Feller TT; Kriener SJ; Witry MJ (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: It has been estimated that 10,000 patient injuries occur in the US annually due to confusion involving drug names. An unexplored source of patient misunderstandings may be medication salt forms. Objective: The objective of this study was to assess patient knowledge and comprehension regarding the salt forms of medications as a potential source of medication errors. Methods: A 12 item questionnaire which assessed patient knowledge of medication names on prescription labels was administered to a convenience sample of patients presenting to a family practice clinic. Descriptive statistics were calculated and multivariate analyses were performed. Results: There were 308 responses. Overall, 41% of patients agreed they find their medication names confusing. Participants correctly answered to salt form questions between 12.1% and 56.9% of the time. Taking more prescription medications and higher education level were positively associated with providing more correct answers to 3 medication salt form knowledge questions, while age was negatively associated. Conclusions: Patient misconceptions about medication salt forms are common. These findings support recommendations to standardize the inclusion or exclusion of salt forms. Increasing patient education is another possible approach to reducing confusion.